2017
DOI: 10.1007/s10865-017-9884-5
|View full text |Cite
|
Sign up to set email alerts
|

Testing a mobile mindful eating intervention targeting craving-related eating: feasibility and proof of concept

Abstract: Theoretically driven smartphone-delivered behavioral interventions that target mechanisms underlying eating behavior are lacking. In this study, we administered a 28-day self-paced smartphone-delivered intervention rooted in an operant conditioning theoretical framework that targets craving-related eating using mindful eating practices. At pre-intervention and 1-month post-intervention, we assessed food cravings among adult overweight or obese women (N = 104; M age = 46.2 ± 14.1 years; M BMI = 31.5 ± 4.5) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 66 publications
3
89
0
5
Order By: Relevance
“…In effect they became more "in-tune" with or aware of the influence of external and internal triggers to eat, obtained distance from the influence of aversive emotions, in effect becoming less reactive, and developed enhanced control over impulsive urges. This explanation can be supported in part by the evidence reviewed regarding the positive effects of mindfulness on varied measures of cue-driven and emotional eating [31,32,44,49,50,[56][57][58][59]. However, until a randomized trial is conducted to disentangle the meditation and educational elements compared to an active control such conclusions warrant cautious interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In effect they became more "in-tune" with or aware of the influence of external and internal triggers to eat, obtained distance from the influence of aversive emotions, in effect becoming less reactive, and developed enhanced control over impulsive urges. This explanation can be supported in part by the evidence reviewed regarding the positive effects of mindfulness on varied measures of cue-driven and emotional eating [31,32,44,49,50,[56][57][58][59]. However, until a randomized trial is conducted to disentangle the meditation and educational elements compared to an active control such conclusions warrant cautious interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study of participants taking the MBSR programme for stress reduction demonstrated a clear reduction in emotional eating scores despite no focus on eating behaviour as part of the intervention [44], though the scale used to assess emotional eating was not validated. An evaluation of an uncontrolled smartphone delivered Mindful Eating programme demonstrated reduction in food craving connected to emotional eating in overweight and obese individuals [49]. A randomized controlled trial of mindfulness-based eating awareness training (MB-EAT) for those with threshold or sub-threshold binge eating disorder revealed a trend level reduction in emotional eating relative to controls [50].…”
mentioning
confidence: 99%
“…Literature searches were conducted in Ovid MEDLINE and Ovid PsycINFO databases in April and October 2017 and were limited to peer-reviewed journal articles published between 2012 and 2017 (including an early online published version). 23 Searches followed the PRISMA statement 24 targeting the following keywords in the title or abstract: (weight OR health OR eat* OR food) AND (technology OR mobile OR app) AND behavio*r. These yielded 257 studies, reduced to 195 after removal of duplicates, which were consequently assessed against inclusion and exclusion criteria. References of eligible studies were manually scanned to identify any additional studies, followed by intercoder agreement checks.…”
Section: Evidence Acquisition Literature Search Proceduresmentioning
confidence: 99%
“…Participants were male or female adults (with the exception of one study that included only females) 23 predominantly from the U.S., with a few studies being conducted in the United Kingdom, 30,31 Australia, 32 New Zealand, 33 and China. 34 Participants in eight of the 17 studies had an increased BMI, with one study including cardiac rehabilitation patients.…”
Section: Nonrandomized Studiesmentioning
confidence: 99%
“…Retest-reliability over two weeks was excellent for the Persian version (r = .92, [81]) and-considering the long time period of six months-was also good for the German version (r = .74, [55]). The FCQ-T-r is also sensitive to change as demonstrated, for example, in decreases of scores during a neurofeedback intervention [86] and during mindful eating interventions [87,88].…”
Section: Modified Versionsmentioning
confidence: 99%